Problems Related to Marketing Research in the Furniture Market of the Republic of Uzbekistan - Azimovna, Musayeva Shoira; Ulugbekovna, Ruzikhulova Nilufar; Abduqayum, Abdukarimov (Research Parks Publishers, 2023)
This article examines the definition of which product category the company equates to, which category it includes, the point of differentiation of the product being positioned, the definition of one or more specific features of the product that clearly differs from the competitor's product, the complexity of the product production process, and the high impact of technology.